SP0109 Rheumatic and Musculoskeletal Diseases (RMDS). (9th June 2015) - Bevan, S.
Abstract : Rheumatic and musculoskeletal diseases (RMDs) are serious non-communicable diseases, representing the primary cause of sickness absence and years lived with disability in Europe. RMDs affect as many Europeans as the population of Germany, Belgium and Austria added together (100 million), curtailing ability to work, labour productivity and employment status. Every year, RMDs diminish the European economy by € 240bn. This lecture will examine the clinical, economic and social impact of RMDs among Europeans of working age and will put forward evidence that early interventions which focus on work as a clinical outcome of care and on work-focused rehabilitation can be cost-effective and reduce productivity losses. Disclosure of Interest: None declared